2020
DOI: 10.1093/nsr/nwaa034
|View full text |Cite
|
Sign up to set email alerts
|

Strategies for engineering advanced nanomedicines for gas therapy of cancer

Abstract: As an emerging and promising treatment method, gas therapy has attracted more and more attention for the treatment of inflammation-related diseases, especially cancer. However, therapeutic/therapy-assisted gases (NO, CO, H2S, H2, O2, SO2, and CO2) and most of their prodrugs lack the abilities of active intratumoral accumulation and controlled gas release, causing limited cancer therapy efficacy and potential side effects. Therefore, the development of nanomedicines to realize the tumour-targeted and controlled… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
107
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 167 publications
(124 citation statements)
references
References 107 publications
0
107
0
Order By: Relevance
“…However, compared to the conventional drug delivery system, the increased complexity may limit its clinical application, although the stimuli-response drug delivery system can improve the targeting efficiency. The potential of the stimuli-response drug delivery system for delivering NO has been explored in other cancer models, and has recently been reviewed in detail [149,150]. However, few pieces of literature were found reporting the implementation of the stimuli-response drug delivery system for the delivery of NO for CRC treatment.…”
Section: Delivery Of No For Targeted Cancer Therapymentioning
confidence: 99%
“…However, compared to the conventional drug delivery system, the increased complexity may limit its clinical application, although the stimuli-response drug delivery system can improve the targeting efficiency. The potential of the stimuli-response drug delivery system for delivering NO has been explored in other cancer models, and has recently been reviewed in detail [149,150]. However, few pieces of literature were found reporting the implementation of the stimuli-response drug delivery system for the delivery of NO for CRC treatment.…”
Section: Delivery Of No For Targeted Cancer Therapymentioning
confidence: 99%
“…PDDN showed effective anti-tumor activity, which indicated that the SO 2 -releasing polymer prodrug was efficient in tumor-killing. The anti-tumor mechanism of SO 2 may be ascribed to the oxidative properties of SO 2 as well as its ability to increase intracellular ROS, which induced the death of the tumor cells [ [25] , [26] , [27] , [28] , [29] ]. At an equivalent drug concentration, the order of the cytotoxicity of the tested formulations was as follows: PDDN-DOX > DOX > PDDN.…”
Section: Resultsmentioning
confidence: 99%
“…Gas therapy refers to the use of gas molecules, such as hydrogen (H 2 ), hydrogen sulfide (H 2 S) and nitric oxide (NO), for treating diseases, which has been recognized as a promising “green treatment” for cancer therapy [ [22] , [23] , [24] , [25] , [26] ]. As a member of the gases family, sulfur dioxide (SO 2 ) has attracted much attention in inhibiting tumor growth in recent years [ [27] , [28] , [29] , [30] , [31] , [32] ].…”
Section: Introductionmentioning
confidence: 99%
“…The 4T1 tumor-bearing mice model was established by injecting 10 7 4T1 cells into the hind limb of each female BALB/c mouse (about 20 g, purchased from Guangdong Medical Laboratory Animal Center). After tumors reached about 100 mm 3 , 100 ÎźL PBS solution (10 mg/kg) of nanoplates was intravenously injected into 4T1 tumor-bearing mice. Main organs (heart, liver, spleen, lung, kidney, and blood) and tumors were extracted at fixed time points (1, 2, 4, 12, and 24 h) post injection.…”
Section: Methodsmentioning
confidence: 99%
“…A variety of nanomaterials are developed as drug carriers to encapsulate drug molecules and deliver them in a targeted way to the diseased site to enhance drug efficacy and reduce drug side effects [1][2][3][4] . As high drug loading capacity as possible is pursued all the way, but is always limited.…”
mentioning
confidence: 99%